Kultur Embrio Tiga Spesies Kopi pada Umur Buah dan Formulasi Media yang Berbeda - Meynarti Sari Dewi Ibrahim; Indah Sulistiyorini (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Studying the fruit age and proper media formulation is one of the important stages in embryo culture of coffee. The data is highly benefical, especially in saving embryos generated from intra- and inter-species crosses that fall prematurely or experience problems in germination. The aim of this study was to determine the suitable age and media formulation for embryo culture of Arabica, Robusta, and Liberica coffee. The study was conducted at the Tissue Culture Laboratory, Indonesian Industrial and Beverage Crops Research Institute from January 2019 to November 2020. Murashige and Skoog (MS) media with growth regulators adapted to embryonic development were used in this study. The three types of coffee divided into 5 groups, namely pinhead, immature, early mature, almost mature, mature, and used as planting material. The research was designed in a completely randomized design with 10 replications, and media formulation as a treatment. The results showed that embryo culture of the three coffee species was conducted successfully, except for pinhead fruit. The older the cultured fruit, the higher the percentage of germination. There is a difference in germination time between the three coffee species. The medium for embryo culture should be adjusted with the age of the fruit being cultured. Aside from growing embryos, the cultured mature fruit embryos on MS medium given 0.5 mg/l BA can also be used for propagation by utilizing the secondary somatic embryos formation.